Physiologic consequences of training - Charlton, G. A.; Crawford, M. H. (Cardiology Clinics, 1997)
Systematic exercise training results in changes in skeletal muscle that increase oxidative capacity and vascular conductance, which lead to an increase in maximal A-VO2. Also, maximal cardiac output is increased, largely because of an increase in maximal stroke volume. Heart rate is decreased at rest and during submaximal exercise because of increased parasympathetic tone and the effect of increased stroke volume on reflex sympathetic tone. The increases in maximal A-VO2 and cardiac output result in increased maximal VO2, the hallmark of the dynamically trained individual. Predominant static exercise training results in fewer increases in maximal VO2 and more local muscle strength enhancements. The systematic application of cross-training can increase both cardiovascular and strength parameters, leading to enhanced athletic performance.